CASK Silence Overcomes Sorafenib Resistance of Hepatocellular Carcinoma Through Activating Apoptosis and Autophagic Cell Death - Ding, Bisha; Bao, Chang; Jin, Luqi; Xu, Liang; Fan, Weimin; Lou, Weiyang (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) patients usually fail to be treated because of drug resistance, including sorafenib. In this study, the effects of CASK in HCC were investigated using gain- or loss-of-function strategies by performing lots of specific methods including Cell Counting kit-8, colony formation assay, flow cytometry, transmission electron microscopy, immunofluorescent confocal laser microscopy and tumor xenograft experiments, immunohistochemistry staining. Currently, we discovered that CASK was positively associated with sorafenib resistance and poor prognosis of HCC. Moreover, inhibition of CASK can increase the effect of sorafenib partially by promoting apoptosis and autophagy, while CASK overexpression presented the opposite results. Besides, all the pan-caspase inhibitor Z-VAD-FMK, autophagy inhibitor 3-Methyladenine (3-MA) and small interfering RNA (siRNA) of LC3B reversed CASK knockout-induced effects with sorafenib treatment, suggesting that both apoptosis and autophagy were involved in CASK-mediated above functions and autophagy played a pro-death role in this research. Intriguingly, similar results were observed in vivo. In molecular level, CASK knockout activated the c-Jun N-terminal kinase (JNK) pathway, treatment with JNK inhibitor SP600125 or transiently transfected with si-JNK significantly attenuated CASK knockout-mediated autophagic cell death. Collectively, all these results together indicated that CASK might be a promising biomarker and a potential therapeutic target for HCC patients.